2016
DOI: 10.1016/j.jcpa.2016.05.003
|View full text |Cite|
|
Sign up to set email alerts
|

Histopathological Characterization of Tail Injury and Traumatic Neuroma Development after Tail Docking in Piglets

Abstract: SummaryTail docking of neonatal pigs is widely used as a measure to reduce the incidence of tail biting, a complex management problem in the pig industry. Concerns exist over the long-term consequences of tail docking for possible tail stump pain sensitivity due to the development of traumatic neuromas in injured peripheral nerves. Tail stumps were obtained post mortem from four female pigs at each of 1, 4, 8 and 16 weeks following tail amputation (approximately two-thirds removed) by a gas-heated docking iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 28 publications
0
35
1
2
Order By: Relevance
“…In addition, tail docking is conducted routinely to prevent tail biting in pigs, but it does not completely eliminate tail biting (Hunter et al, ), especially when pigs are housed in high density and barren environments (Amdi et al, ; Statham, Green, & Mendl, ). Tail docking could cause traumatic neuromas and chronic infection (Herskin, Thodberg, & Jensen, ; Sandercock, Smith, Giminiani, & Edwards, ). The pig's tail has some biological functions, such as expressing its normal behavior and emotional status (Houpt, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tail docking is conducted routinely to prevent tail biting in pigs, but it does not completely eliminate tail biting (Hunter et al, ), especially when pigs are housed in high density and barren environments (Amdi et al, ; Statham, Green, & Mendl, ). Tail docking could cause traumatic neuromas and chronic infection (Herskin, Thodberg, & Jensen, ; Sandercock, Smith, Giminiani, & Edwards, ). The pig's tail has some biological functions, such as expressing its normal behavior and emotional status (Houpt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations in animals have identified the formation of neuromas following tail amputation in dogs 17 , lambs 18 and pigs 1921 . Currently, data on long-term behavioural and physiological consequences of the effect of tail amputation in non-neonatal subjects are lacking in these particular species, however evidence of thermal and mechanical hyperalgesia following tail amputation has been reported in non-neonatal mice 22, 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuromas occur in 10-25% of human amputees, and are generally formed after injury or surgical procedures, resulting in neuropathic pain, residual limb pain, functional impairment and psychological distress (Rajput, Reddy & Shankar 2012), increasing sensitivity to mechanical and thermal stimulation (Toia et al 2015;O´Reilly et al 2016;Yao et al 2017). Histopathological analysis confirmed the presence of neuroma in the tail stump of docked pigs one month after tail docking, characterized by marked nerve sheath and axonal proliferation (Sandercock et al 2016). Moreover, another study in pigs identified age at time of the procedure as a factor that may influence the development of neuropathic pain (Di Giminiani et al 2017).…”
Section: Discussionmentioning
confidence: 89%